PENGEMBANGAN KETERAMPILAN MENULIS KREATIF SISWA SEKOLAH MENENGAH ATAS DALAM PEMBELAJARAN BAHASA ARAB - Zulaika, Siti (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
This study aims to develop a creative writing learning model in Arabic subjects to enhance the kitabah (writing) competence and self-expression of Senior High School students. The research is motivated by students' low interest and difficulties in composing imaginative texts due to monotonous learning methods. Using the Research and Development (R&D) method with the ADDIE model, the study progressed through stages of analysis, design, development, implementation, and evaluation. Data were collected via observations, needs analysis questionnaires, and product testing using pre-tests and post-tests. The results indicate that the developed product, including both instructional materials and new strategies, was declared highly valid by experts. A significant improvement was observed in students' writing abilities, particularly in vocabulary richness, grammatical accuracy, and coherence of ideas. It is concluded that the development of this creative writing model effectively creates a dynamic learning environment and motivates students to produce higher quality, contextual Arabic written works.